Community Behavior on Reproductive Health in Medan Johor, Indonesia - Siti Saidah Nasution (Talenta Publisher, 2020)
The aim of the health promotion is to increase awareness and the individual willingness to have a healthy life for everyone to achieve an optimal degree of public health. The government’s programs in improving positive behavior and reproductive health in the community, especially maternal and infant health, is one of the priorities. Current health problems are focused on the high rates of maternal and infant mortality. This is related to the lack of preparation for couples before marriage and family such as early marriage. The government's initiative to declare pre-marriage as a condition for marriage in 2020 must be socialized and supported by all parties. This research is a descriptive study that aims to describe people's behavior about reproductive health, especially the knowledge and attitudes of adolescents. youths and girls about reproductive health in Medan Johor District. The population is all young people and girls in the Medan Johor sub-district. The sample of teenagers and young people gathered in the Karang Taruna Medan Johor region. Data collection using a questionnaire, which consists of demographic data, knowledge data, and attitudes related to reproductive health. Univariate data analysis used distribution and presentation frequency. The results of the research on knowledge of youth and girls about reproductive health are generally in the low category, namely around 56.4%. The negative attitude is around 62.2%. Health workers must be able to optimize their role in providing health education to the public, especially about reproductive health.